Work readiness, career self-efficacy and career exploration: A correlation analysis - Makki, B.I. (Institute of Electrical and Electronics Engineers Inc., 2015)
The objective of this paper is to investigate the interrelationship between work readiness, career-self-efficacy and career exploration among final year engineering graduates in Malaysia. Data were collected from 325 respondents with a response rate of 45. Pearson correlation analysis was performed to answer the research question. The results indicate a positive significant relationship between work readiness skills, career self-efficacy and career exploration among engineering graduates in Malaysia. The findings of this paper strengthen our argument that acquiring adequate work readiness skills, foster graduates' beliefs in their capabilities and competencies, will lead them toward effective exploration of career choices. Managerial and research implications are discussed. Â© 2015 IEEE.